ANALISIS PENENTUAN HARGA POKOK PRODUKSI BERDASARKAN METODE HARGA POKOK PESANAN (JOB ORDER COSTING) PADA RUMAH KREASI GRIA AIR TEMAM - Judina, Rupia; Triharyati, Eri; Kesuma, Indrawati Mara (Jurnal AkunStie (JAS), 2021)
This study aims to determine the calculation of the cost of raw materials, labor costs, and factory overhead costs based on the cost-of-order method in determining the cost of production at the Home Creations Gria Air Temam in 2020. The type of research used in this study is a qualitative descriptive study. The subject of this research is the creative house of gria water temam, while the object of research is the report on the cost of products with a product sample of painted drums and painted ablution places to determine the cost of production using the job order costing method. The data sources used in this research are primary data and secondary data. The results of the study show that the home creation of Gria Air Temam uses the calculation of the cost of production based on orders but there is an error in determining the imposition of factory overhead costs. The calculation results show a significant difference where the cost of production calculated by the home creation of Gria Air Temam is smaller than the cost of production using job order costing. The difference between the calculation of the company's overhead costs and the theory for the painted ablution place is Rp. 29,851 and the painting drum is Rp. 42,302 where the cost of production for the painted wuduk place according to the company is Rp. 127,000 and the painting drum is Rp. 236,000 while according to the theory it is Rp. 170,351 and the painting drum is Rp. 245,802.